Study on the frequency of single nucleotide polymorphism (rs766432) in BCL11A gene and its association with hematological parameter and HbF level among HbE/β -thalassemia patients in Bangladeshi population - Barno, Shadman Sakib (Brac University, 2022)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2021.